2016
DOI: 10.1016/j.canlet.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A COL11A1-correlated pan-cancer gene signature of activated fibroblasts for the prioritization of therapeutic targets

Abstract: Although cancer-associated fibroblasts (CAFs) are viewed as a promising therapeutic target, the design of rational therapy has been hampered by two key obstacles. First, attempts to ablate CAFs have resulted in significant toxicity because currently used biomarkers cannot effectively distinguish activated CAFs from non-cancer associated fibroblasts and mesenchymal progenitor cells. Second, it is unclear whether CAFs in different organs have different molecular and functional properties that necessitate organ-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 61 publications
8
107
0
Order By: Relevance
“…The up-regulated genes that were most significantly related to disease score in our analysis, COL11A1, COMP, VCAN, FN1, COL1A1 and CTSB have all been associated with cancer progression, poor prognosis and malignant cell invasion in ovarian and/or other cancers (4249). For example, fibronectin promotes ovarian cancer invasion and metastasis through an α5β1-integrin/c-Met/FAK/Src-dependent signaling pathway (44) and COL11A1 and VCAN feature in a 10-gene poor prognostic signature of collagen-remodeling genes regulated by TGF-β signaling in ovarian cancer (45).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The up-regulated genes that were most significantly related to disease score in our analysis, COL11A1, COMP, VCAN, FN1, COL1A1 and CTSB have all been associated with cancer progression, poor prognosis and malignant cell invasion in ovarian and/or other cancers (4249). For example, fibronectin promotes ovarian cancer invasion and metastasis through an α5β1-integrin/c-Met/FAK/Src-dependent signaling pathway (44) and COL11A1 and VCAN feature in a 10-gene poor prognostic signature of collagen-remodeling genes regulated by TGF-β signaling in ovarian cancer (45).…”
Section: Discussionmentioning
confidence: 70%
“…For example, fibronectin promotes ovarian cancer invasion and metastasis through an α5β1-integrin/c-Met/FAK/Src-dependent signaling pathway (44) and COL11A1 and VCAN feature in a 10-gene poor prognostic signature of collagen-remodeling genes regulated by TGF-β signaling in ovarian cancer (45). More recently gene expression of COL11A1 showed a positive association with poor prognosis in several epithelial cancers (49). Importantly, the matrix index appears to correlate with certain immune cell signatures that are also known to influence prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value for estimating patient outcome through molecular subtype assignment (using the molecular prognostic signatures identified by Konecny et al [13]) showed a median survival difference of two years depending on whether the tumor epithelium or stroma and/or mixed tissue is sampled; notably the contribution of the stromal microenvironment to the mesenchymal signature has been recently described [20,22]. Taken together, these observations provide evidence for the existence of a pathological ovarian stroma and the proposed role of cancer-associated fibroblasts contributing to disease development and/or progression [23][24][25][26]. Assignment of the cryopulverized tissue in our study to a particular subtype was less clear due to profound signal averaging of the proteome (Figure 4).…”
Section: Discussionmentioning
confidence: 87%
“…Two markers, Microfibril Associated Protein 5 (MFAP5) and Collagen Type XI Alpha I Chain (COL11A1), have also been suggested to be highly specific CAF‐markers . Their usage is currently still limited amongst the academic community, and further characterization of these markers and their behavior and expression in different tumor types and CAF subtypes is sorely needed.…”
Section: Other Markersmentioning
confidence: 99%
“…Two markers, Microfibril Associated Protein 5 (MFAP5) and Collagen Type XI Alpha I Chain (COL11A1), have also been suggested to be highly specific CAF-markers. 29,55 Their usage is currently still limited amongst the academic community, and further characterization of these markers and their behavior and expression in different tumor types and CAF subtypes is sorely needed. Results obtained by Li et al seem to suggest that MFAP5 expression, at the very least, is not widely conserved between different CAF populations and can significantly vary based on the subtype in question.…”
Section: Other Markersmentioning
confidence: 99%